Case Report: Pulsed field ablation for epicardial right-sided accessory pathway - Haskova, Jana; Peichl, Petr; Borisincova, Eva; Kautzner, Josef (Frontiers in Cardiovascular Medicine, 2024)
We present a case of a 32-year-old male with a history of palpitations and preexcitation on ECG who underwent altogether four failed catheter ablations using different approaches in the two other electrophysiology centers within two years. ECG showed overt preexcitation with a positive delta wave in lead I and negative in leads V1–V3, suggesting a right free wall accessory pathway. During the electrophysiological study, the accessory pathway was localized on the free lateral wall. However, the electrograms and mapping during atrial and ventricular pacing suggested the presence of true epicardial accessory pathway. Repeated radiofrequency energy delivery with the support of the steerable sheath and excellent contact (as assessed by intracardiac echocardiography) at the earliest ventricular activation was not successful. Therefore, the Farawave catheter (Boston Scientific, Inc) was used, and a flower configuration with the intention to cover the entire atrial attachment of the pathway during ventricular pacing was selected. Application of pulsed field resulted in interruption of accessory pathway conduction. An electrophysiological study one year later confirmed the persistent effect of ablation. This case illustrates the potential utility of pulsed field energy for the ablation of atrial insertion of the accessory pathway with an epicardial course. Such an approach can avoid epicardial mapping and access and may improve the safety of the procedure.